Elastic properties of boron carbide films via surface acoustic waves measured by Brillouin light scattering. Issue 3 (11th December 2012) - Salas, E.; Jiménez‐Villacorta, F.; Sánchez‐Marcos, J.; Jiménez Riobóo, R. J.; Muñoz‐Martín, A.; Prieto, J. E.; Joco, V.; Prieto, C.
Abstract Surface acoustic wave (SAW) velocity has been determined by high resolution Brillouin light scattering to study the mechano‐elastic properties of boron carbide films prepared by radio frequency (RF) sputtering. The comparison of experimentally observed elastic behaviour with simulations made by considering film composition obtained from elastic recoil detection analysis‐time of flight (ERDA‐ToF) spectroscopy allows establishing that elastic properties are determined by that of crystalline boron carbide with a lessening of the SAW velocity values due to surface oxidation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>